Can ferroelectric tunnel junction be a game changer as eNVM and in neuromorphic hardware? - Sayani Majumdar (APL Machine Learning)
This work highlights the advantages that ferroelectric tunnel junction (FTJ) memristors can bring to the non-volatile memory technology and in custom designed neuromorphic hardware. Advantages of FTJs not only come from the area-scalability, large on/off switching ratio, fast read and write operations, low-leakage, and high endurance but also from the reduced fabrication complexity and cost perspective. For neuromorphic hardware, depending on specific applications, such as non-volatile or volatile memory operations or programmable synaptic plasticity, specific stack structures can be designed with engineered depolarizing field that can provide flexibility of different time constants of programmed states. Integration of leaky-integrate-and-fire functionality in single-cell FTJs, utilizing accumulative switching and quick depolarizing properties of ferroelectric materials under certain conditions, can lead to an unprecedented reduction in electronic neuron circuit fabrication complexity, making dense integration of neurons and synapses possible on a single chip. The relatively low on current reported in complementary metal–oxide–semiconductor back-end compatible FTJs is a challenge for their fast readout, where innovations on stack and design architectures have shown promising solutions. Large-scale integration of FTJs in memory arrays is required to fully understand the game-changing potential of this technology.